The diagnostic separation of transudates and exudates in pleural effusion - Sunanda, V; Shravanthi, K; Rao, B Prabhakar; Prasad, CN; Satyanarayana, N; Sunitha, P (Journal of College of Medical Sciences-Nepal, 2012)
The present study was undertaken to compare plasma-pleural effusion albumin gradient with Light’s traditional criteria for differentiating exudates from transudate in pleural effusion who were undergoing diagnostic and therapeutic thoracocentesis in whom the etiology of effusion could be determined were studied. Blood and pleural fluid chemistries were measured to determine plasma-pleural effusion albumin gradient and Light’s criteria parameters like pleural fluid proteins, fluid to plasma protein ratio, fluid LDH and fluid to serum LDH ratio and we observed some misclassifications in exudates and transudates. Using an albumin gradient of 1.2 gm/dl or less to indicate exudate and >1.2 gm/dl to indicate transudate, none of the transudates were found to be is misclassifical, but 1 case of exudate (malignant pleural effusion) was misclassifical. We conclude that although Light’s criteria for exudates are very sensitive, albumin gradient of 1.2 gm/dl or less tends to be more specific to exudates. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6705 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 24-28